DESIGN AND THERMAL ANALYSIS OF FIXED AND TRACKING FLAT PLATE COLLECTORS (International Journal of Engineering Sciences & Management Research, 2016)
This paper focuses on Thermal efficiency analysis of flat plate collectors. The instantaneous efficiency for a collector over a day is calculated. Application of solar energy for domestic and industrial heating purposes has been become very popular. However the effectiveness of presently used fixed flat plate collectors is low due to the moving nature of the energy source. In the present work, an attempt has been made to compare the performance of fixed flat plate water heater with that of heater with tracking by conducting experiments. A flat plate water heater, which is commercially available with a capacity of 100liters/day is instrumented and developed into a test-rig to conduct the experimental work. The analysis is carried during which the atmospheric conditions were almost uniform and data was collected both for fixed and tracked conditions of the flat plate collector. The results show that there is an average increase of 400C in the outlet temperature. The efficiency of both the conditions is calculated and the comparison shows that there is an increase of about 21% in the percentage of efficiency.